Uncertainty and the geography of the Great Recession - Stan Veuger; Daniel Shoag (American Enterprise Institute (AEI), 2013)
We create a state-level measure of economic and police uncertainty during the 2007-2009 recession. Despite claims in the literature, the variation in this uncertainty measure matches the cross-sectional distribution of unemployment outcomes in this period. This relationship is robust to numerous controls for other determinants of labor market outcomes and produces a within-state pattern of effects across industries, occupations, and individuals that is consistent with standard "wait-and-see" models of firm behavior under uncertainty. Using preexisting state institutions that amplified uncertainty, we find evidence that this type of local uncertainty played a causal role in increasing unemployment. Together, these results suggest that increased uncertainty contributed to the severity of the Great Recession.
Keywords: A; 330; unemployment; Great Recession; economics